The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.neurobiolaging.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal neuronal networks and seizure susceptibility in mice overexpressing the APP intracellular domain

Abstract: Alterations in the processing of the amyloid precursor protein (APP) lead to familial Alzheimer's disease (AD). AD patients exhibit increased seizure susceptibility and alterations in their EEGs, which suggests that APP and its metabolites may modulate neuronal networks. Here we demonstrate that transgenic mice overexpressing APP intracellular domain (AICD) and its binding partner Fe65 exhibit abnormal spiking events and a susceptibility to induced seizures. These abnormalities are not observed in PDAPP(D664A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 18 publications
8
78
0
Order By: Relevance
“…This is in accordance with earlier findings of others who demonstrated that seizure susceptibility is increased in AD model mice (Westmark et al 2008;Vogt et al 2009), and heat shock proteins can moderate chemically induced seizures (Akbar et al 2003;Ekimova et al 2010). LTP, a cellular correlate of learning and memory (Bliss and Colingridge 1993), was also investigated on hippocampal slices.…”
Section: Discussionsupporting
confidence: 89%
“…This is in accordance with earlier findings of others who demonstrated that seizure susceptibility is increased in AD model mice (Westmark et al 2008;Vogt et al 2009), and heat shock proteins can moderate chemically induced seizures (Akbar et al 2003;Ekimova et al 2010). LTP, a cellular correlate of learning and memory (Bliss and Colingridge 1993), was also investigated on hippocampal slices.…”
Section: Discussionsupporting
confidence: 89%
“…These alterations include reductions in calbindin and increases in neuropeptide Y (NPY; Palop et al 2003;Palop et al 2007). Video electroencephalogram (EEG) telemetry recordings in freely behaving hAPP mice have detected widespread cortical and hippocampal epileptiform activity Minkeviciene et al 2009;Vogt et al 2009;Roberson et al 2011). Some of these EEG studies also documented intermittent, nonconvulsive seizures that were difficult or impossible to detect by visual observation.…”
Section: Disruption Of Cognitive Functions: From Synapses To Neural Nmentioning
confidence: 99%
“…Subsequent neurodegeneration and working memory deficits were also observed in these transgenic mice [96]. In other experiments, similar transgenic mice exhibited abnormal spiking events in their electroencephalograms and susceptibility to kainic acid-induced seizures independent of Aβ [97]. Furthermore, the function of c-Abl kinase in the transcriptional regulation of AICD was reported and c-Abl was shown to modulate AICD-dependent cellular responses, transcriptional induction, as well as apoptotic responses [98].…”
Section: Signaling Functions Of Aicdmentioning
confidence: 74%